Koyee Vowels: An Acoustic Analysis - Rai, Tara Mani (Gipan, 2017)
This paper focuses on the acoustic analysis of Koyee basic vowels. Koyee exhibits basically six vowels. In the acoustic analysis of the basic vowel sounds in the Koyee language, the first formant (F2) are identified as the acoustic analysis cues and they are measured both male and female Koyee speakers individually and in average. The average of F1 and F2 was plotted in F1 versus F2 plane and later compared them plotting them in the same acoustic vowel space. The study shows that female acoustic vowel space is slightly larger than the male. This is because of the differences of the vocal tract of female and male. Although the exact formant frequency values of the vowels produced by male and female speakers varied, the ratio of the difference of the formant frequency values of the different vowels is similar for both male and female speakers. Further, the female voice is more conservative than those of the male speakers because the males are very often in contact with other language speakers.